Decoding The Dynamic of Judicial Decision-Making Experiment: A Bibliometric Exploration - Alima, Azda Fauzia; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This research presents a bibliometric analysis to map the development and direction of research on experiments in decision-making in courts, which focuses on publications indexed in the Scopus database from 1973 to 2024. 1973 was chosen as the start of the period because the first publication was found in that year. Bibliometric analysis methods were used, with data filtered using the Boolean search engine from the Scopus database, and analysis was carried out on June 7, 2024. Tools used for analysis included R, VosViewer, Mendeley, and Microsoft Excel. The results show fluctuations in the number of publications, with the highest peak occurring in 2022-2023 and declining in 2024. Most documents are in the field of Social Sciences, followed by Psychology, Mathematics, and Neuroscience. The United States dominates the most publications, while the main authors who contributed the most include Jones, A., along with several other authors. The University of Nebraska-Lincoln is in the top spot for a number of documents published. This research also provides an overview of research trends and collaboration in this area and can help plan future research.